Missed nursing care and associated factors among nurses and midwives in maternity wards of Sidama region public hospitals, Ethiopia - Tewodros Getachew Tsegaye; Hiwot Tadesse; Gesila Endashaw Yesera; Habtamu Esubalew Bezie; Befekadu Tesfaye Oyato; Sintayehu Solomon Kena; Derese Eshetu Debela; Rediet Belay Andarge (BMC, 2024)
Abstract Background Missed nursing care refers to any aspect of care performed by nursing staff that is omitted or significantly delayed. Even though the potential impact of missing nursing care on maternal and fetal outcomes is significant, there is currently limited evidence regarding the extent of this issue specifically within the maternity wards. Therefore, this study aimed to assess missed nursing care and associated factors in the maternity wards of public hospitals in the Sidama region, Ethiopia 2022. Methods A hospital-based cross-sectional study was conducted among 361 nurses and midwives in maternity wards of Sidama region public hospitals from March 28 to April 26, 2022. Simple random sampling was used to select participants. The data was collected using the MISSCARE survey tool and analyzed with SPSS version 26. Simple linear and multiple linear regression analyses were used to identify the factors associated with missed nursing care. Results The overall mean missed nursing care score was 67 out of 130 (95% CI: 65.92, 68.02) and the average score for each nursing intervention was 2.58 out of 5 (95% CI: 2.54, 2.62). The intention to leave the institution (β = 3.812, 95% CI: 2.285, 5.340) and increasing weekly work hours (β = 0.203, 95% CI: 0.134, 0.272) were factors positively associated with missed nursing care. However, increased work experience (β= -0.963, 95%CI: -1.475, -0.452) and job satisfaction (β= -4.976, 95%CI: -6.431, -3.522) were negatively associated with missed nursing care. Conclusion This study found that the level of missed nursing care was significant. Factors positively associated with missed nursing care included an intention to leave the institution and an increase in weekly work hours. In contrast, an increase in work experience and higher job satisfaction were negatively associated with missed nursing care.